Study Processes and Applications of Ultrasomics in Precision Medicine - Yin, Rui; Jiang, Meng; Lv, Wen-Zhi; Jiang, Fan; Li, Jun; Hu, Bing; Cui, Xin-Wu; Dietrich, Christoph F. (Frontiers in Oncology, 2020)
Ultrasomics is the science of transforming digitally encrypted medical ultrasound images that hold information related to tumor pathophysiology into mineable high-dimensional data. Ultrasomics data have the potential to uncover disease characteristics that are not found with the naked eye. The task of ultrasomics is to quantify the state of diseases using distinctive imaging algorithms and thereby provide valuable information for personalized medicine. Ultrasomics is a powerful tool in oncology but can also be applied to other medical problems for which a disease is imaged. To date there has been no comprehensive review focusing on ultrasomics. Here, we describe how ultrasomics works and its capability in diagnosing disease in different organs, including breast, liver and thyroid. Its pitfalls, challenges and opportunities are discussed.